Development of an integrated ability assessment instrument in reaction rate material - Wan Zahara Zaitu Hania; Hari Sutrisno (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This research aimed to develop a valid and reliable integrated ability assessment instrument (IAAI) to measure the multiple representations and chemical literacy of senior high school students related to the reaction rates. The framework developed in this research was implemented based on a 4-D model (defining, designing, developing, and disseminating). The integrated assessment consisted of five items of essay questions. The preliminary version of the IAAI was initially piloted on reviews by experts, and the paper-pencil test was given to a group of students. The obtained data were analyzed using Item Response Theory (IRT). In addition, Generalized Partial Credit Model (GPCM) model was conducted to examine the parameter quality, which estimated the test items. The content validity, construct validity, and quality of the items suggest that the integrated assessment ability instrument has a high score in validity and reliability. The analysis results of the instrument trial data indicate that the integrated abilities of students are in the medium category.